Sustainable Food Supply by Peri-Urban Diversified Farms of the Agri-Food Region of Central Córdoba, Argentina - Marinelli, María Victoria (2023)
Peri-urban vegetable cropping areas, such as horticultural farms, provide several ecosystem services, such as the provision of fresh food. However, food supply must be estimated on the basis of the current and potential demand of future populations, taking into account the landscape carrying capacity towards sustainable agricultural planning. From this perspective, the study aimed at estimating the resilience of the “Agri-food Region of Central Córdoba” (ARCC) and its role in supporting the provisioning of ecosystem services, such as proximal services, provided by the diversified agricultural landscape in the peri-urban area of Córdoba (Argentina). A direct field survey has been carried out to collect data on the main species and types of crops, the annual productivity, and the area covered by each species and type of horticultural crops. The data have been statistically elaborated to test the spatial and temporal variability of productivity as well as the spatial autocorrelation. In relation to crop diversification, a total of 30 vegetable species have been recorded in the diversified farms under study, with 15 species identified as the most frequent crops as on the basis of the area dedicated to each vegetable species sampled in the farms (in %). The productivity of 30 species has been integrated into a single value of “vegetable crop productivity mean” (kg/m2), proposed and measured in this study, which has been 3.46 kg/m2. It can be a useful monitoring indicator in diversified production contexts. The estimated food supply (ton/year) of vegetable crops for the 170 farmlands has been 72,881 ton/year. An accurate measurement of the biomass harvested on a given surface area can be useful to assign productivity data to the pixel of each land use/cover class, providing accurate input data for remotely sensed-based models supporting decision-making on food provision in peri-urban systems. In this sense, the paper proposes a methodological framework that can be useful worldwide when up-to-date official productivity data are not available, but they are a necessary basis for planning, decision-making, and the implementation of public policies. Thus, diversity in farming systems can combine high ecological and socio-economic benefits, in terms of ecosystem service provision and sustainable food production.